Smile, Sara! and Other Stories: Creating Children’s Picture Books Exploring Emotional Regulation - Vania Jovita Fariman; Stefanny Irawan (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
As the emotional regulation process has already happened since childhood, it is a crucial phase to learn to manage emotions with different strategies. This paper explores emotional regulation strategies performed by children in five children’s picture book stories. The theoretical framework is derived from Emotional Regulation Theory by James Gross. Using antecedent-focused strategies such as situation modification shows better effects than a response modulation strategy such as expressive suppression has negative consequences. As a result of performing expressive suppression strategy, each child character in the stories experiences unpleasant effects such as stress, pessimism, and discomfort with the people around them. The characters then switch to a situation modification strategy by modifying aspects of their initial situation that trigger their negative emotions. All these lead to better consequences of emotional regulation such as experiencing a happier mood and lower levels of negative mood.